Analysis of the Expression and Role of Keratin 17 in Human Tumors - Zhang, Hanqun; Zhang, Yun; Feng, Zhiyu; Lu, Liang; Li, Yong; Liu, Yuncong; Chen, Yanping (Frontiers in Genetics, 2022)
Objective: To explore the expression and carcinogenic effect of KRT17 in human tumors, and to provide useful information for the study of KRT17.Methods: We used databases including TCGA, GEO, GTEx and GEPIA2 to analyze the expression, mutation and prognosis of KRT17 in human tumors. Through webservers, including UALCAN, TIMER2.0 and STRING, we learned about the genetic variation, immune cell penetration and enrichment analysis of KRT17-related genes.Results: KRT17 was highly expressed in most tumors (such as esophageal cancer, lung cancer, cervical cancer, etc.), and the high expression level correlated with tumor stage and prognosis.In addition, amplification was the main type of KRT17 tumor variation, with an amplification rate of about 9%, followed by mutation, with a mutation rate of 4%.Moreover, KRT17 was strongly associated with tumor-infiltrating immune cells (such as Macrophages,CD8+T, Tregs, and cancer-associated fibroblasts).KEGG analysis suggested that KRT17 may play a role in tumor pathogenesis following human papillavirus infection, and GO enrichment analysis indicated that the carcinogenicity of KRT17 can be attributed to cadherin binding, intermediate fibrocytoskeleton and epidermal development.Conclusion: KRT17 may play an important role in the occurrence, development and prognosis of malignant tumors. We provided a relatively comprehensive description of the carcinogenic role of KRT17 in different tumors for the first time.